MANUSCRIPT EVIDENCE FOR ALPHABET-SWITCHING IN THE WORKS OF CICERO: COMMON NOUNS AND ADJECTIVES. (15th January 2019) - O'Sullivan, Neil
Abstract : Of the hundreds of Greek common nouns and adjectives preserved in our MSS of Cicero, about three dozen are found written in the Latin alphabet as well as in the Greek. So we find, alongside συμπάθεια, also sympathia, and ἱστορικός as well as historicus. This sort of variation has been termed alphabet-switching; it has received little attention in connection with Cicero, even though it is relevant to subjects of current interest such as his bilingualism and the role of code-switching and loanwords in his works. Rather than addressing these issues directly, this discussion sets out information about the way in which the words are written in our surviving MSS of Cicero and takes further some recent work on the presentation of Greek words in Latin texts. It argues that, for the most part, coherent patterns and explanations can be found in the alphabetic choices exhibited by them, or at least by the earliest of them when there is conflict in the paradosis, and that this coherence is evidence for a generally reliable transmission of Cicero's original choices. While a lack of coherence might indicate unreliable transmission, or even an indifference on Cicero's part, a consistent pattern can only really be explained as an accurate record of coherent alphabet choice made by Cicero when writing Greek words.